2005
DOI: 10.1300/j115v24n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Digital Chat Reference in Health Science Libraries

Abstract: Digital reference service adds a valuable new dimension to health science reference services, but the road to implementation can present questions that require carefully considered decisions. This article incorporates suggestions from the published literature, provides tips from interviews with practicing academic health science librarians, and reports on data from students' exploration of academic health science library Web sites' digital reference services. The goal of this study is to provide guidelines to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Because this definition does not try to define the two parties involved in the reference interaction (both Dee and Newhouse [2005] and Moyo [2002] cite the librarian and the user of that library), it may be applied to e-mail, chat, and reference interactions in a virtual world such as Second Life. It is particularly relevant to virtual worlds where those seeking reference help may not be the "real life" users of the library, but rather information-seekers from anywhere in the world.…”
Section: Digital Referencementioning
confidence: 99%
“…Because this definition does not try to define the two parties involved in the reference interaction (both Dee and Newhouse [2005] and Moyo [2002] cite the librarian and the user of that library), it may be applied to e-mail, chat, and reference interactions in a virtual world such as Second Life. It is particularly relevant to virtual worlds where those seeking reference help may not be the "real life" users of the library, but rather information-seekers from anywhere in the world.…”
Section: Digital Referencementioning
confidence: 99%
“…A survey of academic health science libraries showed 22 percent (n = 132) of libraries reporting had added chat reference as a service point from 2002 to 2004. 99 In another study, librarians compared vendor-based chat with IM chat and these findings add some nuance to the story. 100 Over the 12 month period of data collection, the library maintained their vendor-based chat and introduced IM chat.…”
Section: A Mission Objectives Statement Of Purposementioning
confidence: 99%
“…Straw (2001) believed asynchronous reference services were beneficial to libraries as they expanded the reach of service into the community. Dee (2005) found asynchronous service critical to students, especially if the institution did not offer other types of digital reference. A survey of 706 University of Iowa students showed that 71.3% believed Web/e-mail reference service were more important than other library services (Dew, 2000, p. 121).…”
Section: Advantages Of Asynchronous Reference Servicesmentioning
confidence: 99%
“…Tenopir further determined that the use of e-mail allowed for a more in-depth investigation of the question. Dee (2005) stated that of the 132 academic health science libraries studied, 80 libraries offered only asynchronous reference (p. 26). Some libraries also preferred e-mail reference to chat reference because of staffing concerns or low usage of chat service (Dee;Thomsett-Scott, 2004).…”
Section: Advantages Of Asynchronous Reference Servicesmentioning
confidence: 99%
See 1 more Smart Citation